Dimensions of human nutrition - Karaboue, Karidia (Progress in Nutrition, 2023)
The food literature, encompassing historical, bioethical, anthropological, psychological and sociological contributions, appears to be vast, even though the various psychological and social implications of human eating behavior rarely come up in everyday life and are often taken for granted unchecked in their assumptions. One need only think of one’s daily life to realize that food is not just an object to be consumed and subjected to dietary or qualitative analysis but has a cultural, symbolic and relational character that goes beyond its mere nutritional value and the human need to eat. For this reason, food practices are worthy of cultural analysis, discussion and interpretation. Nutrition is one of the significant issues of our time, and food should rightly be considered the most important issue for humanity. It is almost always the most critical factor for most people.